2003
DOI: 10.1271/bbb.67.455
|View full text |Cite
|
Sign up to set email alerts
|

In vivoVisualization of the Distribution of a Secretory Protein inAspergillus oryzaeHyphae Using the RntA-EGFP Fusion Protein

Abstract: A fusion gene encoding ribonuclease T 1 -EGFP (rntAegfp) was constructed and expressed to use it as a tool for studies on the secretory pathway in Aspergillus oryzae. The successful secretion of the intact RntA-EGFP fusion protein was detected by ‰uorescence measurement and Western analysis. With use of the RntA-EGFP system, we were able to see high ‰uorescence at hyphal tips and observe concentrated ‰uorescence at septa in basal cells during growth at optimal conditions. Cold or heat shock during growth cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…3C and D). Moreover, these observations were consistent with the known septal localization patterns of secretory hydrolytic enzymes fused with (E)GFP, such as the RNase of A. oryzae (27) and the glucoamylase of A. niger (9). The dispersed, round structures observed in the ⌬Aovps10 strain were attributed to accumulation of the fusion protein at unknown organelles ( Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…3C and D). Moreover, these observations were consistent with the known septal localization patterns of secretory hydrolytic enzymes fused with (E)GFP, such as the RNase of A. oryzae (27) and the glucoamylase of A. niger (9). The dispersed, round structures observed in the ⌬Aovps10 strain were attributed to accumulation of the fusion protein at unknown organelles ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…The Vps10p receptor has also been implicated in the targeting and delivery of several recombinant proteins from the late-Golgi compartments to vacuoles for degradation by the vacuolar protease complex (11,12). In our previous work, secreted protein RNase T 1 (RntA) fused with enhanced green fluorescent protein (EGFP), RntA-EGFP, was visualized in the vacuoles, as well as in the hyphal tips (27), indicating that a portion of the expressed heterologous proteins was presumably transported into the vacuoles for degradation. These observations suggest that for the improvement of heterologous protein production in A. oryzae, it is necessary to elucidate the machinery which mediates protein trafficking between the Golgi apparatus and vacuoles.…”
mentioning
confidence: 99%
“…Thus, we hypothesized that hfm-21 secretes CPY-EGFP via a vesicle-mediated, conventional secretory pathway similar to the one used for extracellular enzymes. Unlike glucoamylase-green fluorescent protein fluorescence (9) and RNase T1-EGFP fluorescence (12), however, CPY-EGFP fluorescence was not observed at the septa. Therefore, the vesicles transporting CPY-EGFP or ␣-amylase may be distinguishable from those transporting glucoamylase or RNase T1 in this mutant.…”
Section: Discussionmentioning
confidence: 81%
“…3). However, the Spitzenkörper where the secretory proteins accumulate (Gordon et al, 2000;Harris et al, 2005;Hayakawa et al, 2011;Kimura et al, 2010;Masai et al, 2003) could not be observed at the hyphal tips.…”
Section: Cloning Of Aosedd and Localization Analysis Of Aosedd-egfpmentioning
confidence: 90%